Tujuan Umum Hukum Islam dari Individu Hingga Negara : Analisis Normatif terhadap Implementasi Bimbingan Pra-Nikah di Indonesia (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The steady increase in divorce cases in Indonesia suggests that many couples begin married life without adequate emotional, financial, or intellectual readiness. In response, the government encourages premarital education as a preventive initiative designed to equip future spouses with the skills needed to manage potential domestic difficulties. Viewed through the lens of maqāṣid al-sharī‘ah, this initiative supports the essential goals of Islamic law, namely the promotion of well-being at the personal, family, community, and national levels. This study argues that premarital education reflects the core principles of Islamic legal ethics and functions as a normative expression of the sharī‘ah. Using a normative-theoretical legal framework combined with a maqāṣid al-sharī‘ah analysis, the research engages Qur’anic and Hadith texts, classical and modern fiqh discussions, uṣūl al-fiqh, Indonesian regulatory provisions on premarital counseling, and scholarly works on Islamic Family Law. The results show that major triggers of marital breakdown emotional instability, financial pressure, recurring disputes, and limited understanding of marital responsibilities can be reduced through structured premarital education. These programs strengthen spiritual awareness, emotional resilience, communication skills, conflict-resolution abilities, and economic management. Consequently, premarital education becomes a strategic mechanism for nurturing harmonious households and reinforcing the framework of Islamic Family Law in Indonesia, positioning it as a sharī‘ah oriented tool vital for contemporary social welfare.